Lonchaeinae (Diptera: Lonchaeidae) of Czechoslovakia - present state of faunistics. - Morge, Günter; Máca, Jan (Contributions to Entomology = Beiträge zur Entomologie, 1986)
A survey of the faunistic knowedge of Czechoslovak Lonchaeinae is given. Earomyia schistopyga Collin, E. tomskensis Morge, Lonchaea corusca Czerny und L. scutellaris Rondani are given from Czechoslovakia for the first time; L. contigua Collin, L. limatula Collin, L. obscuritarsis Collin and L. patens Collin are new for Bohemia, Chaetolongchea pallipennis (Zetterstedt) and Longchaea postics Collin are new for Moravia. Some previously undocumented records from some Czechoslovak countries are presently foundet by newly collected documentary material; this concerns Protearomyia nigra (Meigen), Chaetolongchea dasyops (Meigen) and Lonchaea palposa Zetterstedt from Bohemia, Lonchaea seitneri Hendel from Moravia and L. sylvatica Beling from both Bohemia and Moravia. On the other hand, documentary material of Eraomyia inquilina (Hendel in Seitner) and laticornis Meigen from Czechoslovakia, L. seitneri Hendel and L. tarsata Fallén from Bohemia, as well as of Chaetolongschaea dasyops (Meigen) and Longschaea palposa Zetterstedt from Moravia is probably not preserved. In L. deutschi Zetterstedt and L. contraria Czerny the determination of the Czechoslovak material is uncertain and L. albigena Collin was previusly recorded from Czechoslovakia by error. Earomyia tomskensis Morge is restituted as valid species and the female of Earomyia virilis Collin is revealed for the first time. Nomenclatural Acts tomskensis Morge, 1959 (Earomyia), stat. rev. recently a valid species, not a synonym of Earomyia bazini Séguy, 1932